“Jazykovoj” (Language) Versus “Lingvisticheskij” (Linguistic): Etymology, Semantics, Usage - Olga. S Kryukova; Maria B. Rarenko (RUDN Journal of Language Studies, Semiotics and Semantics)
The authors deal with the issue of distinguishing between the use of the adjectives “jazykovoj” (language) versus “lingvisticheskij” (linguistic) in modern Russian, in the professional sphere of communication as well. The relevance of the study is determined by the recent increase in the cases of incorrect use of these adjectives not only by ordinary native speakers of the Russian language, but also by experts - philologists and representatives of other humanitarian areas. Incorrect use of adjectives “jazykovoj” (language) versus “lingvisticheskij” (linguistic) in special scientific literature as part of terminological combinations (lingvisticheskij konflikt (linguistic conflict), lingvisticheskie sposobnosti rebenka (linguistic abilities of the child), lingvisticheskaja bezopasnost’ (linguistic security), etc.) entails the consolidation of dubious collocations from the point of view of the language norm, the appearance of ambiguity in the texts, and the blurring of the terminological system as a whole. The purpose of the article is to clarify the use of the adjectives “jazykovoj” (language) versus “lingvisticheskij” (linguistic). The material of the study was authentic texts in Russian, data from authoritative dictionaries of the Russian language, personal observations of the authors of the article. Separate phrases are considered, which include adjectives “jazykovoj” (language) versus “lingvisticheskij” (linguistic), their origins, meanings, usages are analyzed. The research methods were descriptive, comparative and comparative methods, as well as the method of component analysis. The main results of the study are that many phrases used today as stable combinations, as well as phrases used as terms, are borrowed from the English language or through its mediation. In modern English, the adjective linguistic has two meanings in authoritative explanatory dictionaries (unlike the similar Russian adjective “lingvisticheskij” (linguistic) - related to linguistics (science)): 1) related to language, 2) related to linguistics (science), which largely explains the appearance in the Russian language of such phrases as lingvisticheskij kapital (instead of jazykovoj kapital), lingvisticheskaja problema (instead of jazykovaja problema, if we are talking about language, and not about linguistics), lingvisticheskij konflikt (instead of jazykovoj konflikt), etc.